The use of digital photographs to quantify vegetation ground cover in degraded areas - Azevedo, Marinete Martins; Leite, Laércio Leonel; Baptista, Gustavo Macedo de Mello (Sociedade & Natureza, 2005)
This study was aimed at assessing the possibility to use digital photographs to evaluate success of the reclamation of a gravel-mined degraded area. The indicator used to measure success was the degree of vegetation ground cover. Photographs were taken with a Canon camera (model Power Shot A 100). On 11th of October 2003, in a sunny day (without clouds), a total of 24 photographs were taken of the centre of the 24 experimental plots. All the 24 photographs were processed with ENVI 3.5 software following the same procedures applied to process satellite scenes. In each scene analysed, two classes - vegetation cover and bared soil - were identified with the maximum likelihood algorithm. Results showed that digital photographs can be used in the quantification of vegetation ground cover and that the technique employed in this study can be applied to evaluate methodologies of reclamation of mined areas in which the establishment of vegetation is expected. The technique tested in this study can be employed by government agencies in charge of land reclamation plans because it is efficient in determining vegetation ground cover, is easy to perform and is not expensive.